Doctor Who. The complete tenth series [videorecording (Blu-Ray)] - Moffat, Steven, 1961-; Capaldi, Peter; Mackie, Pearl, 1987-; Lucas, Matt, 1974- (BBC Worldwide Americas, 2017)
In New York, with brain-swapping aliens poised to attack, the Doctor and Nardole link up with an investigative reporter and a mysterious masked superhero known only as the Ghost. Can the Doctor save Manhattan? When the Doctor, Bill and Nardole become trapped on a space station without oxygen, they discover the spacesuits are trying to kill them.